Evaluation of Corrosion Inhibition Performance of Zinc Oxide and Sodium Nitrite in Quarry Dust Concrete - Devi, M.; Kannan, K. (Asian Journal of Chemistry, 2013)
The objective of this study is to discuss the inhibitive behaviour of two inorganic corrosion inhibitors namely sodium nitrite, an anodic inhibitor and zinc oxide, a cathodic inhibitor on steel embedded in concrete containing quarry dust as fine aggregate. Each inhibitor was evaluated for various strength properties such as compressive strength, split tensile strength, flexural strength and bond strength in addition to water absorption capacity. The performance of the inhibitors on corrosion resistance was studied using impressed voltage method, rapid chloride ion penetration test, AC impedance measurement and weight loss measurement. The surface analysis of the embedded steel was carried out by scanning electron microscope analysis. Based on the results of strength and durability tests the optimum percentage of inhibitors to be added in quarry dust concrete was determined. The experimental results demonstrate that addition of inhibitors enhances the corrosion resistance properties and does not have any adverse effects on strength properties.